Efficiency index used to assess shoulder stress in college softball pitchers throughout a simulated game - Nebel, A. R.; Fava, A. W.; Bordelon, N. M.; Oliver, G. D. (ISBS Proceedings Archive (Michigan), 2023)
Shoulder distraction forces in softball pitching are known to have a positive impact on performance yet a negative impact on musculoskeletal health. The purpose of this study was to assess changes in shoulder stress across innings pitched using Efficiency Arm-Stress Index (EASI) scores. Motion capture was used on collegiate softball pitchers pitching a simulated game. Peak shoulder distraction force was obtained using inverse dynamics procedures and used to calculate an EASI score (fastball velocity divided by peak shoulder distraction force in percent body weight). A RM·ANOVA revealed inning had no effect on EASI score (F[6,7]=1.28, p=0.286). Understanding a pitcher`s efficiency score may help shape individual pitching loads. Future work should investigate clinically meaningful changes in efficiency scores and mechanisms behind low efficiencies.